What rhymes with reason [videorecording (DVD)] - Thiessen, Sean; Griffith, Gattlin; Hurtado, Ricardo, 1999-; Torres, Giselle, 2002-; Marzett, LaRonn; Burgess, Katie; Graterol, Juan Carlos, Jr; Johnson, Bart, 1970- (Kino Lorber, 2024)
Tragedy ignites a group of teens to find a legendary landmark hidden in the wilderness. Together, they navigate the adventure while confronting the darkness within themselves. Channeling teen classics like The Goonies and The Breakfast Club, the story wrestles with depression, anxiety, doubt, and identity. What Rhymes with Reason sparks a fun and emotional tale of hope for the whole family.